Kefir and champagne vinegar to defeat bacterial vaginosis in woman, avoiding oral metronidazole, clindamycin and bothersome douchings - Piotr Brzezinski; Lorenzo Martin (Our Dermatology Online, 2018)
Scope ouf our study is to treat with natural remedies vaginitis in woman, when it has been detected the disease originates from bacterical assault (Gardnerella vaginalis and/or Streptococca spp.) in order to avoid the administration of perilous antibiotics and elicit sexual desire and eliminate pain during urination in the woman who has suffered from this disease after 4-5 days only. We have to proceed with the preliminary phase of a simplest test (the ammin whiff test) and determine the type of vaginitis and thus treat it using champagne or cider vinegar to adjust mucosal pH and kefir, a fermented beverage, that is extremely rich in mesophyllic bacteria, apt to reveal an important and suggestive function regard vaginal microbes.